AN ANALYSIS OF TEACHER’S TEACHING GRAMMAR APPROACHES USED FOR TEACHING PAST TENSE AT KRESNA ENGLISH LANGUAGE INSTITUTE IN PARE KEDIRI - Sarif Idiganir (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2018)
This study analyzed teachers’ teaching grammar approach in teaching past tense to HP 2 levels class at Kresna English Language Institute in Pare Kediri. The researcher chose Kresna because many people said that Kresna is a good course for grammar. The aims of this study were to describe teachers’ approaches in teaching past tense. The method of this research was descriptive qualitative research. The respondents of this research were two English teachers teaching past tense at Kresna English Language Institute in Pare Kediri. The data were collected through interview guide. The findings of this research were both teachers achieved three indicators: presentation, oral or written practice, and identifying the rule of the pattern. It can be concluded that two teachers used the deductive approach in teaching grammar especially teaching past tenses.